Making farmer programming smarter: The Farm Radio approach [Ghana] - Yeboah, Alfred; Ohene, Rosemond (Technical Centre for Agricultural and Rural Cooperation, 2018)
Suppliers of radio extension programmes in Ghana have been supported by Farm Radio International to make their programmes more participatory and engaging for smallholder farmers. With access to interactive, accurate, timely and interesting information, farmers have reported increased yields and incomes. Radio broadcasters have also been able to make their radio programming more financially sustainable.